Conceptual Design of Ethnomathematics-Based Student Worksheets at The Keraton Kesultanan Kadariah Pontianak - Khairunnisa; Restiana Pernanda; Marhadi Saputro (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2022)
Ethnomatematics can be used as an alternative method for teachers in facilitating learning so that students understand mathematics more easily. By ethnomathematics it is hoped that students can further improve their critical thinking, metacognitive, and problem solving abilities. The aims of this study were (1) to describe the conceptual design of Ethnomatematics-based Ethnomatematics Mathematical Worksheets at the Keraton Kesultanan Kadariyah Pontianak, to introduce the mathematical concepts found in Keraton. This research is a type of literature study. The instruments used in this study were questionnaires, and validation sheets. Based on the literature review that has been carried out, ethnomatematics-based student worksheet should be used in learning process.